Improving attractiveness of an insect pest through value-addition : A possible insect management strategy - Shadung, Kagiso Given (University of Limpopo ( Turfloop campus), 2012)
Attractiveness of insect pest for use as sources of food may be improved by providing information on preservation and relevant nutritional value. Nutritional composition in edible insects may depend on drying method and/or vegetation (location). Influence of drying method and location on nutritional composition of the African metallic wood boring beetle (Sternocera orissa), widely consumed in certain rural communities of Limpopo Province, South Africa, was investigated. Randomised complete block design in a 3 x 3 factorial arrangement was used with three drying methods (oven-drying, freeze drying, cooking method) and three locations (Khureng, Magatle, Ga-Masemola), with three replicates. Nutritional composition data were subjected to a two-way analysis of variance (ANOVA) and means were separated using Turkey Honestly Significant Differences (HSD) at 5 % level of significance. Relative to freeze-drying, oven-drying and cooking methods increased protein, carbohydrates, fat, energy, ash and dry matter content with the exception of cooking method, which decreased the moisture content. Compared to other locations, Ga-Masemola significantly increased fat and energy of the test beetle. Relative to the freeze-drying method, oven-drying and cooking increased (P ≤ 0.05) essential and non-essential amino acids. Location did not have significant effect on the essential and non-essential amino acids of S. orissa across all the villages. Similarly, oven-drying and cooking increased K, P, Fe, Zn and Mg. Compared to locations, Ga-Masemola increased (P ≤ 0.05) Fe of the test beetle. Results of the study suggested that oven-drying and cooking methods improved the nutritional composition of S. orissa, which has the potential of enhancing nutrition in marginal rural communities of Limpopo Province. Providing results of this study to rural communities through extension services has the potential of improving the attractiveness of this beetle to marginal communities, and thus, increasing harvesting and therefore, reduce insects population densities.
Thesis (M.Sc. (Plant Protection)) --University of Limpopo, 2012
Keywords: Insect pest; Insect management strategy; 641.396; Insects as food